A scheme for connecting vehicular networks to the Internet. Issue 5 (31st October 2013) - Xiaonan, Wang; Haili, Huang; Hongbin, Cheng; Rong, Zhou
Abstract: This paper proposes a scheme for connecting vehicular networks to the Internet protocol version 6‐based Internet. In this scheme, the architecture based on road domains is proposed in order to reduce the mobility handover frequency. Based on this architecture, the distributed address configuration algorithm for vehicular networks is proposed. In this algorithm, a vehicle obtains a unique address from the nearest access point (AP) without duplicate address detection. Based on this architecture, the routing algorithm based on the geographical position is proposed. The routing algorithm is performed in the link layer, and a vehicle achieves the communication with the Internet via the nearest AP. As a result, the communication delay is shortened. In this scheme, a vehicle is always identified by its home address, and during the mobility process, it does not need to be configured with a care‐of address. Therefore, the packet loss caused by the address change is avoided. Moreover, during the mobility handover process, a vehicle can receive the data from the same AP, so the packet loss rate is substantially reduced. This paper evaluates the performance of the proposed scheme, and the data results show that this scheme shortens the communication delay and lowers the packet loss. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : In this scheme, the architecture based on road domains is proposed in order to reduce the mobility handover frequency. Based on this architecture, the distributed address configuration algorithm for vehicular networks and the routing algorithm based on the geographical position are proposed. In this scheme, a vehicle is always identified by its home address, and during the mobility process, it does not need to be configured with a care‐of address.